Status and groups - Thomas-Hunt, Melissa C.; Wageman, Ruth (Emerald, 2005)
This seventh volume of Research on Managing Groups and Teams examines the effects of status on individuals and groups. At the most basic level status describes the rank of individuals or groups within a specified context. It refers to the prestige hierarchy which determines, which individuals or groups are afforded honor and respect and are, consequently, given opportunities to influence outcomes. The authors in this volume consider both the role of status within groups and how the status of groups within their larger context affects members and overall group effectiveness. Consequently, the works presented here consider the relationship between the status of individuals and groups, the treatment they receive, and their participation within their immediate environment; the link between exhibited behaviors and status conferral; and the emergence and effects of status rivalries within and across groups, including challenges to existing status hierarchies. This book will be of particular interest to individuals interested in understanding the effects of status on individuals and the groups and organizations in which they are embedded.
Keywords: Teams in the workplace.; Social status.; elektronické knihy; electronic books